Does nurse-based case management for aged myocardial infarction patients improve risk factors, physical functioning and mental health? The KORINNA trial. (29th August 2020) - Hunger, Matthias; Kirchberger, Inge; Holle, Rolf; Seidl, Hildegard; Kuch, Bernhard; Wende, Rupert; Meisinger, Christine
Abstract: Background: Older patients with acute myocardial infarction (MI) are often lacking optimal support to continue rehabilitation after discharge from hospital. The objective of the study was to examine whether a home-based case management programme led by nurses can improve atherogenic risk factors, physical functioning, and mental health in the first year following discharge. Methods: The KORINNA study is a randomized two-armed parallel group trial including 329 patients (aged 65–92 years) from the Augsburg Hospital in southern Germany. The intervention consisted of an individualized follow-up programme with a duration of 1 year, including home visits and telephone calls. The control group received usual care. Secondary outcome measures included clinical parameters (blood pressure, lipid parameters), functional status measures, cognitive status, depressive symptoms, and nutrition risk. Results: At 1-year follow up, patients in the intervention group ( n  = 116) had significantly better low-density lipoprotein cholesterol levels (−8.4 mg/dl, 95% CI –16.4 to −0.4), hand grip strength (+2.53 kg, 95% CI 0.56 to 4.50), and SCREEN-II nutrition risk scores (+2.03, 95% CI 0.58 to 3.48) than patients in the control group ( n  = 136). The intervention group also had better mean scores with regard to self-reported disability, activities in daily living, and mental health, but differences were not always significant and meaningful. Conclusions: The results of the KORINNA study indicate that nurse-based case management can improve blood lipid levels, functional status, and nutrition risk of aged patients with MI.